Improving Cognitive Abilities in Early Childhood Through Color Experimental Method: A Case Study of Kindergartens in Muna Regency: Improving Cognitive Abilities in Early Childhood Through Color Experiments - Eni Afrianti; Afifah Nur Hidayah; Salwiah (Primary Education Insight, 2025)
Improving cognitive abilities in early childhood is a crucial aspect of early childhood education because it forms the foundation for learning readiness at subsequent educational levels. This study aimed to analyze improvements in the cognitive abilities of children aged 5–6 years through the application of the color experiment method in learning activities. The study employed a classroom action research approach with a two-cycle design, with each cycle comprising planning, action implementation, observation, and reflection. The participants were 14 children aged 5–6 years. Research instruments included observation sheets for teacher and child activities, assessment sheets for children’s cognitive abilities, limited interviews, and documentation of learning activities. Data were analyzed using descriptive quantitative and qualitative approaches. The results revealed a significant improvement in children’s cognitive abilities from the initial observation to cycle II. Class-level cognitive achievement increased to 92.85% in cycle II, exceeding the predetermined success indicators. In addition, teachers’ instructional activities and children’s learning engagement also improved substantially following refinements in learning strategies. These findings indicate that the color experiment method is effective in enhancing children’s cognitive abilities. The improvement was not limited to mastery of color concepts but also included the development of logical thinking, understanding of cause-and-effect relationships, and the ability to communicate observational outcomes. This study highlights the importance of implementing hands-on, experiential learning as an innovative strategy in early childhood education to optimize children’s cognitive development.